1996
DOI: 10.1046/j.1365-2265.1996.646467.x
|View full text |Cite
|
Sign up to set email alerts
|

FSH isoforms: bio and immuno‐activities in post‐menopausal and normal menstruating women

Abstract: These results show that, in normal women, circulating FSH bioactivity is associated with isoforms with different oligosaccharide [correction of oligosacharide] structures according to hormonal status. FSH in the follicular phase has a higher degree of branching and a more complete carbohydrate chain than the FSH secreted during the menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Less acidic isoforms, which presumably possess relatively low amounts of sialic acid residues and greater amounts of high mannose-and hybrid-type oligosaccharides (Creus et al 1996), exhibited a greater capability to induce expression of cytochrome P450 arom mRNA and tPA mRNA and protein than the variants bearing more complex, highly sialylated oligosaccharides. The mechanism(s) subserving these differences in potency among the isoforms is uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less acidic isoforms, which presumably possess relatively low amounts of sialic acid residues and greater amounts of high mannose-and hybrid-type oligosaccharides (Creus et al 1996), exhibited a greater capability to induce expression of cytochrome P450 arom mRNA and tPA mRNA and protein than the variants bearing more complex, highly sialylated oligosaccharides. The mechanism(s) subserving these differences in potency among the isoforms is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…The main difference among the various isoforms is caused by charge, which in FSH is mainly determined by its content in terminal sialic acid residues (Chappel et al 1983, Baenzinger & Green 1988, Ulloa-Aguirre et al 1995, although differences in nonterminal carbohydrates also play an important role in determining the heterogenous nature of the several members of the glycoprotein hormone family (Ulloa-Aguirre et al 1988b, Papandreou et al 1993, Creus et al 1996. We and others have found that the receptor binding activity of the intrapituitary FSH isoforms varies depending on the charge of the isoform (Stanton et al 1992, Ulloa-Aguirre et al 1992, Yding Andersen et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we found that it was the relative proportion of these two types of glycosylation variants that were more affected by changes in ovarian cyclicity and ageing in normal women. FSH glycoforms, bearing triantennary and bisecting oligosaccharides, circulate in the follicular phase of the normal menstrual cycle, when a fully functional gonad is present; however, they are absent in postmenopausal women (Creus et al 1996, Velasquez et al 2006. During the perimenopause, there is a relative decrease in circulating FSH glycoforms bearing triantennary and bisecting oligosaccharides, concomitantly with the appearance of a small proportion of glycosylation variants bearing high mannose and hybrid-type oligosaccharides (Loreti et al 2009).…”
Section: Distribution Profile Of Native Rhfsh Glycoforms After Concanmentioning
confidence: 99%
“…The presence of N-acetylglucosamine residues, frequently present in glycoproteins bearing biantennary and truncated carbohydrate chains, considerably weakens binding to the lectin, weakly bound fraction: WB (Goldstein et al 1965). The technique described by Narasimhan et al (1979), modified by Cheng et al (1984) and Creus et al (1996), was employed. Briefly, equilibrium buffer (50 mm Tris-HCl; pH 7.4, 0.5 M NaCl, 1 mM MgCl 2 , 1 mM CaCl 2 , and 1 mM MnCl 2 ) was used to elute unbound rhFSH glycoforms (rhFSH-UB); equilibrium buffer containing 10 mM methyl-a-D-glucopyranoside (glucoside) was used to elute the weakly bound rhFSH glycoforms (rhFSH-WB) and equilibrium buffer containing 0.1 M methyl-a-D-mannopyranoside (mannoside) was used to elute the firmly bound rhFSH glycoforms (rhFSH-FB).…”
Section: Cona Chromatographymentioning
confidence: 99%
“…FSH is encoded by a single gene, but the pituitary is capable of making more than 17 different isoforms of FSH through post-translational modifications (14). Alteration of the carbohydrate sulfonation and sialylation patterns can lower the pH of the protein and increase the half-life of the isoform.…”
Section: Discussionmentioning
confidence: 99%